Productive Waqf Performance Audit Model: The Perspective of Maqāṣid Sharia and MSME Empowerment - Chrisna, Heriyati; Suryani, Yani; Siregar, Lukman Hakim (Journal of Management, Economic, and Accounting, 2025)
Wakaf produktif has a significant potential for improving the overall economy through the development of productive and synergistic wakaf aset with UMKM; nevertheless, systematic work audits with syariah kerangka maqāṣid are still very rare. The goal of this study is to develop a kinerja audit model for productive wakaf instruments with the perspective of maqāṣid syarīʿah and UMKM. This audit model integrates the following three maqāṣid goals: ad-dīn, an-nafs, al-ʿaql, an-nasl, and al-māl, as well as UMKM indicators (modal, akses pasar, pelatihan, jaringan, keberlanjutan), as well as quantitative and qualitative pengukuran mechanisms, pelaporan, and akuntabilitas. The primary contribution of the study is to provide a comprehensive, syariah-based kinerja audit for the production organization in order to promote social-economic cooperation.